Use of force in international law - Eishan Jan, Mohammad Naqib (CLJ Publication, 2011)
This book, consisting of ten chapters, provides succinctly the essential aspects of the 'Use of Force in International Law'. It analyses the history of the UN Charter, its conception and role in today’s world. Their member States and the provisions on the concept of the use of force are also scrutinised. The book proceeds to discuss the protection of human rights and the difficulties some States may face in abiding with the rules of international law, whilst at the same time trying to protect the rights of their citizens, which includes protection of women and foreigners.